The second coming of what? - Blume, Harvey (American Prospect, 2000)
A review of an article entitled “The Second Coming—A Manifesto,” by David Gelernter, is presented. Gelernter, a surviving victim of the Unabomber, continues on from the concepts expressed in his first book in describing a debate about the value of technology from the standpoint of technophile and technophobe. He moves beyond this dichotomy and contends that digital technology will not always disrupt lives with uproar about innovation. The article has the same facility with language and the same abundance of ideas and new angles of attack that are characteristic of Gelernter's writings, but the social theory that he relies upon is not original. Gelernter is an agent of the modernity he disdains, but his constantly reiterated theory of “the coup of the intellectuals” bars him from getting a grasp on the forces shaping America.